Autoimmune diseases and immunosuppressive therapy in relation to the risk of glioma. (10th December 2019) - Anssar, Tareq M.; Leitzmann, Michael F.; Linker, Ralf A.; Meier, Christoph; Becker, Claudia; Jick, Susan; Sahm, Katharina; Platten, Michael; Hau, Peter; Seliger, Corinna
Abstract: Effectors from the immune system can modulate the course and possibly the early development of gliomas. We, therefore, hypothesized that autoimmune diseases associated with increased immune‐surveillance may also modulate the risk of human glioma. To test this hypothesis, we used data from the well‐validated Clinical Practice Research Datalink (CPRD) GOLD from the UK to analyze the association of immune‐related disorders or use of immunosuppressive drugs and the risk of glioma. We identified 3112 incident glioma cases diagnosed between 1995 and 2017. We randomly selected up to 10 controls, matching them to glioma cases on age, sex, index date, general practice, and number of years of active history in the database prior to the index date. We performed conditional logistic regression analyses to estimate Odds Ratios (ORs) of glioma among those exposed to allergies, autoimmune diseases, and immunosuppressive drugs. Overall, we found no materially altered association between a history of any autoimmune disease (OR 0.98, 95% CI 0.86‐1.11), allergy (OR 0.97, 95% CI 0.89‐1.05), or use of immunosuppressive drugs and the risk of glioma. However, subgroup analyses among younger patients found a statistically significant increased risk of glioma in patients with a history of inflammatory bowel disease (IBD) (OR 2.59, 95% CI 1.31‐5.12). There was also an inverse association between asthma and risk of glioma in patients with longer survival (OR 0.73, 95% CI 0.58‐0.91) and between long‐term duration diabetes and risk of glioma (OR 0.71, 95% CI 0.53‐0.96). Abstract : The immune system is increasingly recognized as a key player in glioma pathobiology. Small case‐control studies have found inverse associations between autoimmune diseases and glioma incidence. We performed a large case‐control study, which did not replicate these associations. However, our data indicate that inflammatory bowel disease (IBD) among patients ≤40 years are associated with an increased risk of glioma. Further studies are needed to explore the role of IBD and altered microbiota in glioma.